KELAYAKAN USAHA BUDIDAYA IKAN NILA DI DESA CIBUNAR KABUPATEN SUMEDANG: SEBUAH ANALISIS KEBERLANJUTAN - Agnita Ratnasari; Ramadhani Eka Putra; Tien Lastini (University of Jember, 2021)
Tilapia from small-scale farms has a low level of business sustainability due to high energy and financial investment. This study aims to analyze the business feasibility and sustainability status of tilapia cultivation in Cibunar Village, Sumedang Regency, This study uses a survey method for 100% of the existing population (16 respondents). Business feasibility is determined by calculating the investment feasibility analysis (NPV; IRR; PP and B/C Ratio) and the sustainability status analysis is carried out using the RAPFISH-MDS method. The results showed that the tilapia fishery business was feasible to run as a business seen from the NPV (Net Present Value) of Rp36.297.168; IRR of 27.70%; Net B/C Ratio 1,51; and PP (Payback Period) at 3 years 11 months 24 days, BEP/BEP production (units) of 151,65 kg and BEP (Sales) of Rp 4.549.373,48. The value of the sustainability index of tilapia cultivation based on the ecological dimension is 75,37 (very sustainable); economic dimension 55,27 (sufficiently sustainable); institutional dimension 33,49 (less sustainable); social dimension 46,94 (less sustainable) and technological dimension 13,7 (unsustainable). The sustainability status of tilapia aquaculture in Cibunar Village, Sumedang Regency, in a multidimensional manner is 44,85 (less sustainable).